Evaluation of the Forensic Reports Documented at the Department of Forensic Medicine of Gaziantep University 2005-2011 - Akbaba, Murat; Isır, Aysun Baransel; Karaarslan, Bekir; Dülger, Hikmet Ergin (The Bulletin of Legal Medicine, 2014)
Objective: In this study, it is aimed to discuss the forensic cases which were documented in our department to create regional databases by revealing the properties of substance use, sociodemographic characteristics of forensic reports, event types and sexual crimes and to discuss with other similar studies. Material and methods: Forensic reports which were documented between 2005-2011 years at the Department of Forensic Medicine of Gaziantep University Medical Faculty were examined retrospectively and a total of 5524 forensic reports included into the study. Results: Analysis of the types of the forensic cases revealed that assaults and batteries constituted most of the cases 1136 (20,6%) and the remaining cases were respectively; traffic accidents 960 (17,4%), stab wounds 863 (15,6%), gunshot wounds 463 (8,4%), drug abuse 540 (9,8%), sexual abuse 423 (7,7%) and unspecified injuries 395 (7,2%). Conclusion: We think that revealing of forensic case profiles is very important to uncover the underlying problems and the real causes of social problems to be able to produce efficient and rational solutions. Keywords: Forensic Report; Assaults and Batteries; Stab Wound; Traffic Accident; Sexual Abuse